Answer:
Step-by-step explanation:
[tex]7x=4x^{2} -1[/tex]
[tex]7x - (4x^{2} -1)= 0[/tex]
[tex]7x - 4x^{2} +1 = 0[/tex]
[tex]-4x^{2} +7x+1=0[/tex]
[tex]4x^{2} -7x-1=0[/tex]
use the quadratic formula: [tex]x = \frac{ -b \frac{+}{-} \sqrt{b^{2} -4ac }}{2a}[/tex]
a = 4 b = -7 c = -1
·[tex]x = \frac{-(-7)\frac{+}{-} \sqrt{(-7)^{2}-4 times 4(-1)} }{2 times 4}[/tex]
[tex]x = \frac{7\frac{+}{-} \sqrt{49-16} }{8}[/tex]
[tex]x = \frac{7\frac{+}{-} \sqrt{65} }{8}[/tex]
hope this helped!
mark me brainliest :D